Investigation of Using Various Quantities of Steelmaking Waste for Scavenging Hydrogen Sulfide in Drilling Fluids - Ashraf Ahmed; Salaheldin Elkatatny; Sagheer A. Onaizi (Geofluids, 2022)
Effective in situ scavenging of hydrogen sulfide (H2S) while drilling a sour formation is critical for limiting the prevalent related impacts and safety hazards. Thus, it is necessary to develop a specialized additive that can selectively react with H2S and remove it without generating harmful byproducts or impairing drilling fluid performance. Additionally, waste management and utilization will transfer the waste from being an environmental and economic burden to a valuable commodity. Accordingly, we report herein the management of steelmaking waste through its utilization as a novel H2S scavenger for water-based drilling fluids, as well as the evaluation of the effects of the steelmaking waste dosage (1, 2, and 3 g) on the mud H2S scavenging capability and key properties. The H2S scavenging capacity of the waste-containing mud was investigated and compared to that of the base mud and fluids containing the commercial scavengers (triazine- and iron gluconate-based materials). In addition, the mud rheology, alkalinity, and filtering performance were studied in the presence and absence of the waste, and the findings were compared to those of commercial scavengers. This study showed that adding 1, 2, and 3 g of the steelmaking waste to the base drilling fluid significantly improved the H2S scavenging capacity by 105, 399, and 503%, respectively, while the triazine- and iron gluconate-based materials increased the capacity by 179 and 131%. Similarly, when the proportion of the steelmaking waste increased, the rheological parameters, comprising apparent viscosity, plastic viscosity, and yield point, slightly increased. The inclusion of the steelmaking waste reduced mud pH to 10.4, 9.8, and 8.5 with a content of 1, 2, and 3 g, respectively, compared to 11.0 for the base mud, 11.1 for triazine-based material, and 7.9 for iron gluconate-based scavenger. When 1 and 2 g of the steelmaking waste were added, the obtained filtrated liquid volume was preferably lower than the base mud and even the commercial scavengers-contained muds. As a result, 2 g of steelmaking waste could be added for enhanced mud performance. Nevertheless, higher amounts of the steelmaking waste could be used instead to achieve maximal H2S scavenging capability, with an extra alkalinity controller added to ensure attaining the practical recommended properties.